2000
DOI: 10.1063/1.372520
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelastic dependence of switching field in TbFe–FeCo giant magnetostrictive spring-magnet multilayers

Abstract: Articles you may be interested inStress-mediated magnetoelectric memory effect with uni-axial TbCo2/FeCo multilayer on 011-cut PMN-PT ferroelectric relaxor J. Appl. Phys. 113, 17C719 (2013); 10.1063/1.4795440 Perpendicular giant magnetoresistance composed of [ Co ∕ Pt ] multilayer and CoFe ∕ TbCo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Further results on structure and magnetic behavior are given elsewhere. [5][6][7][8][9] The results on the FePd system are preliminary in nature, and detailed studies will be reported in a later manuscript. The FePd and FePd/ Fe multilayers were deposited by dc magnetron sputtering in Ar pressure ranging from 3 mTorr to 10 mTorr and power from 30 to 120 W. The composition of the FePd films was varied either by sputtering Fe-30 at.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Further results on structure and magnetic behavior are given elsewhere. [5][6][7][8][9] The results on the FePd system are preliminary in nature, and detailed studies will be reported in a later manuscript. The FePd and FePd/ Fe multilayers were deposited by dc magnetron sputtering in Ar pressure ranging from 3 mTorr to 10 mTorr and power from 30 to 120 W. The composition of the FePd films was varied either by sputtering Fe-30 at.…”
Section: Methodsmentioning
confidence: 91%
“…Kneller's exchange-spring mechanism 4 is a striking illustration of how the switching fields can be reduced and strain susceptibility enhanced. [5][6][7][8][9] While Kneller initially described the exchangespring mechanism to develop magnets, exchange coupling can also be used to decrease the switching field, which is proportional to the ratio of anisotropy K to saturation magnetization M s . 10 This is achieved by sandwiching high switching field actuator thin films between high magnetization, soft magnets such as Fe or Fe 50 Co 50 .…”
Section: Introductionmentioning
confidence: 99%
“…6(a). The behavior can be explained using a theoretical expression postulated by Chopra on the basis of a magnetic collinear structure [15]. Applying this to the present case, the coercivity can be described as follows: Fig.…”
Section: Magnetization Loops Of Different Singe Filmsmentioning
confidence: 98%
“…[1][2][3] In an exchangespring magnetic system, the soft magnetic phase exhibits magnetization reversal prior to the magnetization reversal in the hard magnetic phase due to a strong magnetic exchange coupling. 4 A large number of exchange-spring systems studied are multilayers of RE-Fe 2 /(R*Fe 2 or TM), where RE ¼ rare earth elements, R* ¼ Y, and TM ¼ Fe and Co. [5][6][7][8][9][10][11][12][13][14] In these layered systems, the film's thickness ratio (t S /t H ) and/or the materials anisotropy is used to modify the coercivity/remanence values and cannot be modified once manufactured. However, many RE-Fe 2 materials exhibit strong magnetoelastic coupling 15 suggesting that the magnetic anisotropy can be changed in-situ by applying an external mechanical load (or applying an electric field induced strain), thereby tuning the exchange-spring phenomenon and/or the coercivity/remanence values.…”
Section: Introductionmentioning
confidence: 99%